2008
DOI: 10.1185/030079908x260952
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic insulin aspart 30 treatment in patients with type 2 diabetes poorly controlled on prior diabetes treatment: results from the PRESENT study

Abstract: According to this observational study, in clinical practice, initiating or transferring uncontrolled patients to biphasic insulin aspart improved glycaemic control without using a strict insulin algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…Although it is always necessary to exercise care when adjusting the insulin dose, and to pay attention to possible interactions with coadministered drugs, the characteristics of BIAsp 30 suggest that it may be possible to increase the dose slightly, and reduce HbA1c levels further without increasing the incidence of hypoglycemic episodes. Since several previous studies [13][14][15][16][17][18] , some of them were conducted in Japanese patients, have shown that BIAsp 30 improved HbA1c/daily glycemic profiles equally versus multiple insulin injection therapy or better than previous OAD therapy in insulinnaïve patients. Hypoglycemic episodes were not increased versus these regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is always necessary to exercise care when adjusting the insulin dose, and to pay attention to possible interactions with coadministered drugs, the characteristics of BIAsp 30 suggest that it may be possible to increase the dose slightly, and reduce HbA1c levels further without increasing the incidence of hypoglycemic episodes. Since several previous studies [13][14][15][16][17][18] , some of them were conducted in Japanese patients, have shown that BIAsp 30 improved HbA1c/daily glycemic profiles equally versus multiple insulin injection therapy or better than previous OAD therapy in insulinnaïve patients. Hypoglycemic episodes were not increased versus these regimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, intensive insulin therapy whilst improving glycemic control is associated with increased risk of hypoglycemia leading to significant morbidity and mortality. 20 Hypoglycemia may have particularly serious outcomes in elderly or frail people with type 2 diabetes. The incidence for severe hypoglycemia has been reported to be 11.8 and 0.9 events per 100 patient-years for patients with type 2 diabetes treated with insulin and sulfonylureas respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They provide peaks of plasma insulin aspart to control postprandial blood glucose (PPBG) levels, as well as a steady flow of basal, protaminated insulin to maintain glucose control between meals. In a large observational study of patients with type 2 diabetes, BIAsp 30 has shown greater improvements in glycaemic control in insulin-naïve patients than in patients previously treated with insulin 11 . Furthermore, HbA 1c targets were reached with a lower dose of BIAsp 30 compared with insulin pre-treated patients.…”
Section: Introductionmentioning
confidence: 95%